A policy analysis of digital strategies: Brisbane vs. Vancouver. (2015) - Alizadeh, Tooran
A growing number of cities around the world have now realised the need to strategically capitalise on the rapidly growing digital economy. In mid-2013, cities of Brisbane, Australia and Vancouver, Canada both released their 'Digital Strategy' documents to strengthen their economy by enhancing digital connections amongst citizens, business, and the whole city as a digital organisation. The paper critically investigates the digital strategies developed for the two cities to understand how they utilise the potentials of the digital economy in their respected cities and regions. The results identify fundamental differences in the two documents' core focus that firstly define different roles for the digital strategies in Brisbane vs. Vancouver, and secondly could highly affect the implications of the strategies for the two cities' overall economic development. Nevertheless, both Vancouver and Brisbane are still in the early days of implementing their digital strategies, and the paper has to be understood as a prelude to further empirical investigation.